2014
DOI: 10.1242/jeb.103986
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent variation in gas exchange patterns and spiracular control in Rhodnius prolixus

Abstract: Insects display an array of respiratory behaviors, including the use of discontinuous gas exchange. This pattern is characterized by periods of spiracular closure, micro-openings (flutter), and complete openings during which the majority of gas exchange takes place. A current model of insect spiracular control suggests that spiracles are controlled by two interacting feedback loops, which produce the discontinuous pattern. The flutter period is thought to be initiated by a critically low partial pressure of ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Low O 2 in the ganglion signals the spiracle to open (Burkett and Schneiderman, 1974;Förster and Hetz, 2010). By contrast, high CO 2 affects the spiracle muscle directly (Case, 1956), either by interfering with the transmission of action potentials at the neuromuscular junction (Badre et al, 2005;Hoyle, 1960), or by diffusing into muscle cells and disturbing local pH (Förster and Hetz, 2010;Grieshaber and Terblanche, 2015;Heinrich and Bradley, 2014). Wigglesworth (1935) showed that fleas perfused with high levels of lactic acid exhibited high-frequency (5-15 oscillations per minute) fluctuations in some spiracles.…”
Section: Patterns Of Respiratory Exchangementioning
confidence: 99%
“…Low O 2 in the ganglion signals the spiracle to open (Burkett and Schneiderman, 1974;Förster and Hetz, 2010). By contrast, high CO 2 affects the spiracle muscle directly (Case, 1956), either by interfering with the transmission of action potentials at the neuromuscular junction (Badre et al, 2005;Hoyle, 1960), or by diffusing into muscle cells and disturbing local pH (Förster and Hetz, 2010;Grieshaber and Terblanche, 2015;Heinrich and Bradley, 2014). Wigglesworth (1935) showed that fleas perfused with high levels of lactic acid exhibited high-frequency (5-15 oscillations per minute) fluctuations in some spiracles.…”
Section: Patterns Of Respiratory Exchangementioning
confidence: 99%
“…Different blood-sucking arthropod species have been analysed in terms of metabolic activity, such as fleas, bedbugs, ticks and mosquitoes (Lighton et al, 1993;Bradley, 2003, 2006;DeVries et al, 2013). However, the species that has been best characterized in terms of respiration dynamics and metabolism is the triatomine Rhodnius prolixus Bradley, 2009, 2010;Rolandi et al, 2014;Heinrich and Bradley, 2014). Hence, this bug constitutes a good model system with which to evaluate the energetics of feeding in blood-sucking insects.…”
Section: Introductionmentioning
confidence: 99%
“…the metabolic response that accompanies meal ingestion, digestion, absorption and assimilation (Secor, 2009), when we focused on the effect of digestion on the metabolic rate of R. prolixus, we registered a postprandial metabolic scope of 2. Previous work on 5th instar nymphs of R. prolixus showed metabolic scope values of almost 8 and 14 (Bradley et al, 2003;Heinrich and Bradley, 2014). These higher values previously found could be explained by the larger amount of blood ingested by nymphs compared with adult males, together with the effects of other physiological processes such as development and moulting, which occur following feeding.…”
Section: Research Articlementioning
confidence: 77%